2017
DOI: 10.5219/702
|View full text |Cite
|
Sign up to set email alerts
|

The influence of variety on the content of bioactive compounds in beetroot (Beta vulgaris L.)

Abstract: Vegetable are widespread throughout the world and is a major part of the human diet. From the perspective of agricultural crops that belong to the group of Beta vulgaris (beetroot, mangold, sugar beets, fodder beet) are first-rate vegetables. Especially popular is used in the food industry for the production of sugar, various vegetable juices, coloring agents, and many other products. Beetroot (Beta vulgaris L.) is considered one of the ten most important vegetable in the world, thanks to the content of rare n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Furthermore, Ninfali and Angelino (2013) reported total phenols of 1.77 mg GAE g −1 DW (equivalent to 177 mg GAE 100 g −1 DW) [ 58 ], which was lower than the values found in the current study. Kovarovič et al (2017) investigated the total phenolic compounds of four beetroot varieties in the Czech Republic and noted the range of 368.75 ± 5.14 mg kg −1 (equivalent to 36.87 mg 100 g −1 DW) to 887.75 ± 7.73 mg kg −1 (equivalent to 88.77 mg 100 g −1 DW) belonging to the variety Chioggia (white-colored with red strips) and Cylindra, respectively [ 59 ]. Kavalcova’ et al (2015) stated a total polyphenols’ range of 820.10 mg kg −1 to 1280.56 mg kg −1 (equivalent to 82.01–128.05 mg 100 g −1 DW) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Ninfali and Angelino (2013) reported total phenols of 1.77 mg GAE g −1 DW (equivalent to 177 mg GAE 100 g −1 DW) [ 58 ], which was lower than the values found in the current study. Kovarovič et al (2017) investigated the total phenolic compounds of four beetroot varieties in the Czech Republic and noted the range of 368.75 ± 5.14 mg kg −1 (equivalent to 36.87 mg 100 g −1 DW) to 887.75 ± 7.73 mg kg −1 (equivalent to 88.77 mg 100 g −1 DW) belonging to the variety Chioggia (white-colored with red strips) and Cylindra, respectively [ 59 ]. Kavalcova’ et al (2015) stated a total polyphenols’ range of 820.10 mg kg −1 to 1280.56 mg kg −1 (equivalent to 82.01–128.05 mg 100 g −1 DW) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data in Figure 2f represents anthocyanins content (790 mg/l) of beetroot juice which is in accordance with the previous findings of Manea (2013) who analyzed bioactive compounds in beetroot juice during preservation by refrigeration and found that fresh beetroot juice contained 0.54 g/L anthocyanins content. Kovarovic et al (2017) reported varied content of anthocyanin (14.48 to 84.50 mg/kg) in five varieties of beetroot.…”
Section: Beetroot Juicementioning
confidence: 99%
“…The blood-brain barrier has an active efflux through a monocarboxylate transporter in order to avoid aluminum deposition in the brain. However, this system can be affected by increasing the concentration of aluminum in the blood Reduction in serum aluminum concentration in treated group could be as a result of beetroot or broccoli extract interaction with the aluminum possibly by chelation to cause its elimination from the blood [29].…”
Section: C1 Reg Controlmentioning
confidence: 99%